Efek Sari Tomat Ceri (Solanum lycopersicum var.cerasiforme) dalam Pengencer Air Kelapa (Cocos nucifera L.) pada Semenbabi Landrace - Nancy D. F. K. Foeh; Heny Nitbani; Mariana Febrilianti Resilinda Putri; Veronika Serapian Pangu Nae (JURNAL KAJIAN VETERINER, 2025)
The use of fresh semen in artificial insemination quickly leads to a decline in quality if an appropriate extender is not added. A suitable extender functions to protect spermatozoa during processing and storage, thereby prolonging their viability. Additionally, incorporating fruit juices rich in antioxidants can help neutralize free radicals and minimize cellular damage. Semen wascollected froma 2–4-year-old male pig using a dummy. High-quality semen was then divided into two control groups (K0 and K1) and five treatment groups consisting of varying volumes of cherry tomato juice: 20µL, 40µL, 60µL, 80µL, and100µL, all mixed coconut water extender and stored at preservation temperature. Sperm motility was evaluated every two hours for a total of 16 hours. The findings indicated that the coconut water extender combined with cherry tomato juice antioxidants significantly influenced (p<0.05) the motility percentageof Landrace boar spermatozoa. The addition of 60µL cherry tomato juice (Solanum lycopersicum var. cerasiforme) produced the best results in maintaining sperm quality, with a motility value of 67.00±0.79% and a viability duration of up to 16 hours.